ANALISIS METODE EXPONENTIAL UNTUK MENGUKUR SENSITIVITAS HARGA OBLIGASI KORPORAT AKIBAT PERUBAHAN TINGKAT SUKU BUNGA (Studi Empiris Pada Obligasi Korporat di Indonesia Periode Januari-Juni 2009) - Prihanisetyo, Adi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2010)
Bond is one of the alternatives for investment in money market. As another invesment in other instrument (stock), investment in bond also has risk which bond holders need to observemeticulously. As we know from bond theory that the change of interest rate is one of the metioned risk. The bond holders must observe the effect of interest rate and bond profit rate. These two factors have direct link, when there is a change of interest rate, the expected profit by investors also changes.This study to analysis the relation between the change of interest rate with yield using approch of duration and convexity and then compared with the approach is always more accurate than traditional approach by seeing error score yield, if we compare the price of bond prediction with the price of bond in the market, Livingston and Zhou ( 2003). The samples in this study use corporate bonds data with fixed coupons for the period of January â€“ June, 2009 which can be found in Indonesia Stock Exchange. The method of statistics used is Independent Sample t-test for hypothesis test. From statistical calculation it can be concluded that there is a different estimation of bond price using traditional with exponential, whereas the duration plus convexity method is the best method to use because it has a mean squere error (MSE) is the smallest among the traditional methods of duration, the exponential methods of duration, and method of traditional duration plus convexity equal to 65,8696.Â